Transperineal Ultrasonography in Perianal Crohn Disease: A Valuable Imaging Modality - Emily K Wright; Kerri L Novak; Cathy Lu; Remo Panaccione; Subrata Ghosh; Stephanie R Wilson (Canadian Journal of Gastroenterology and Hepatology)
Aims of treatment for Crohn disease have moved beyond the resolution of clinical symptoms to objective end points including endoscopic and radiological normality. Regular re-evaluation of disease status to safely, readily and reliably detect the presence of inflammation and complications is paramount. Improvements in sonographic technology over recent years have facilitated a growing enthusiasm among radiologists and gastroenterologists in the use of ultrasound for the assessment of inflammatory bowel disease. Transabdominal intestinal ultrasound is accurate, affordable and safe for the assessment of lumi-nal inflammation and complications in Crohn disease, and can be performed with or without the use of intravenous contrast enhancement. Perianal fistulizing disease is a common, complex and often treatment-refractory complication of Crohn disease, which requires regular radiological monitoring. Endoanal ultrasound is invasive, uncomfortable and yields limited assessment of the perineal region. Although magnetic resonance imaging of the pelvis is established, timely access may be a problem. Transperineal ultrasound has been described in small studies, and is an accurate, painless and cost-effective method for documenting perianal fluid collections, fistulas and sinus tracts. In the present article, the authors review the literature regarding perineal ultrasound for the assessment of perianal Crohn disease and use case examples to illustrate its clinical utility.